2012
DOI: 10.3892/ijo.2012.1367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and diagnostic relevance of hypermethylated in cancer 1 (HIC1) CpG island methylation in renal cell carcinoma

Abstract: Abstract. The tumour suppressor gene hypermethylated in cancer 1 (HIC1) is a transcriptional repressor, which functionally cooperates with p53. Loss of HIC1 function is associated with the development of various tumor entities. The aim of this study was to elucidate the relevance of CpG island (CGI) methylation of HIC1 in renal cell carcinoma (RCC). DNA methylation of HIC1 was analysed in a total of 98 tumor and 70 tumor adjacent normal specimens. After conducting bisulfite conversion, relative methylation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Moreover, HIC-1 expression was found to be silenced in triple-negative breast cancer [24]. Although studies have identified HIC-1 as having frequent changes in hypermethylation or loss of heterozygosity in many human cancers [40, 41], the molecular mechanisms through which HIC-1 inhibits cancer progression remain poorly understood. HIC-1 is a multifunctional, sequence-specific transcriptional repressor that interacts with several major repression and chromatin remodeling complexes [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HIC-1 expression was found to be silenced in triple-negative breast cancer [24]. Although studies have identified HIC-1 as having frequent changes in hypermethylation or loss of heterozygosity in many human cancers [40, 41], the molecular mechanisms through which HIC-1 inhibits cancer progression remain poorly understood. HIC-1 is a multifunctional, sequence-specific transcriptional repressor that interacts with several major repression and chromatin remodeling complexes [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylated in cancer-1 ( HIC1 ), a tumor suppressor gene essential to mammalian development [4], is located in the chromosomal regions 17p13.3, and is telomeric to the TP53. In many different human cancers (including prostate [57], hepatocellular [8, 9], pancreatic [10], renal cell carcinoma [11], breast cancers [12] and esophageal cancers [13], HIC1 is epigenetically inactivated but not mutated [14]. The methylation status of the HIC1 promoter is also associated with tumorigenesis and poor survival in patients with medulloblastomas [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hypermethylation of RASSF1A and HIC in patients with RCC is associated with a poor prognosis [79, 80]. …”
Section: Methodsmentioning
confidence: 99%